WAYS TO INCREASE STOCK TRADING IN THE CAPITAL MARKET (World Economics and Finance Bulletin, 2025)
This article examines the various ways to increase stock trading activity in the capital market, focusing on enhancing market liquidity, transparency, and investor participation. In modern financial systems, active stock trading is a key indicator of a healthy and dynamic capital market that supports efficient resource allocation and corporate financing. The study identifies several drivers of increased trading, including improvements in market infrastructure, regulatory reforms, digital trading platforms, and the development of diversified financial instruments. Special attention is given to expanding the investor base through financial literacy programs, incentivizing institutional participation, and ensuring real-time access to market information. Comparative analysis of global capital markets reveals that countries with higher trading volumes typically exhibit stronger investor protections, transparent disclosure systems, and advanced technological integration. The article concludes by proposing a set of policy recommendations aimed at reducing market barriers, boosting investor confidence, and fostering sustainable growth in stock trading, thereby contributing to the overall development of the capital market
Keywords: Stock trading; capital market; market liquidity